2011
DOI: 10.1080/00221325.2010.504761
|View full text |Cite
|
Sign up to set email alerts
|

Do Children Realize That Pretend Emotions Might Be Unreal?

Abstract: This research is aimed at comparing children's understanding of the distinction between external and internal emotion in deception and pretend play situations. A total of 337 children from 4 to 12 years of age participated in the study. Previous research suggests that in deception situations this understanding is very rudimentary at the age of 4 years, whereas 6-year-olds can articulate it in words. In the present work the children were asked to make this distinction in pretend play or deception tasks. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 36 publications
0
15
1
8
Order By: Relevance
“…The primary aim of the present study was to provide the first test of children’s ability to discriminate the authenticity of two negative facial expressions, sad and fear, as well as happy expressions, in 8–12 year olds relative to adults. We tested 8–12 year olds because, by 8 years of age, children have a good conceptual understanding of the difference between genuine and pretend expressions ( Sidera et al, 2011 ). We tested sad and fearful expressions specifically because these were the only two negative expressions for which we were able to obtain genuine-pretend stimulus pairs from the same identity models (created using the Miles/McLellan method), and for which adults had already demonstrated ability to discriminate authenticity (for sad, consistently above chance in five studies), or at least some evidence of ability to discriminate authenticity (for fear, above chance in one out of the two previous studies).…”
Section: Introductionmentioning
confidence: 99%
“…The primary aim of the present study was to provide the first test of children’s ability to discriminate the authenticity of two negative facial expressions, sad and fear, as well as happy expressions, in 8–12 year olds relative to adults. We tested 8–12 year olds because, by 8 years of age, children have a good conceptual understanding of the difference between genuine and pretend expressions ( Sidera et al, 2011 ). We tested sad and fearful expressions specifically because these were the only two negative expressions for which we were able to obtain genuine-pretend stimulus pairs from the same identity models (created using the Miles/McLellan method), and for which adults had already demonstrated ability to discriminate authenticity (for sad, consistently above chance in five studies), or at least some evidence of ability to discriminate authenticity (for fear, above chance in one out of the two previous studies).…”
Section: Introductionmentioning
confidence: 99%
“…There are several emotions that can be studied in this area but sadness, anger and happiness are the first labels acquired by children (Widen & Russell 2003;Maassarani, Gosselin, Montembeault, & Gagnon, 2014). In terms of understanding false emotion though, happiness was discarded because previous research showed that children have more difficulty differentiating internal from external feelings in pretend play situations where the protagonists were pretending to be happy while being in fact sad (see Sidera et al, 2011). The reason for this might be that children are reluctant to accept that others feel sad while pretending to be happy.…”
Section: Language and Tom In Children With Hearing Lossmentioning
confidence: 99%
“…In addition, these two emotions are the first two negative emotions that children usually recognize (Widen, 2013), and may therefore also be the first ones to be interpreted in terms of pretend emotions. The emotion of happiness is usually the first to be labeled by children in free labeling tasks (Widen, 2013), but Sidera et al (2011) pointed out methodological difficulties when studying children's understanding of pretend happiness (children might interpret that pretending to be happy makes one actually happy), so we decided not to include pretend happiness in the present research.…”
Section: Children's Recognition Of Emotional Expressionsmentioning
confidence: 99%